Myths and imaginaries of feminist digital activism. Meme analysis of the #FuckGenderRoles cybercampaign - Sola-Morales, Salomé; Hernández-Conde, Macarena; Arencón-Beltrán, Sandra; Sierra Caballero, Francisco (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2021)
The Internet and social media are essential tools for contemporary cyberfeminism. Through New Information and Communication Technologies (ICTs), feminisms express and share ideas, proposals, and emotions, as well as creating a feeling of belonging and collective identity. A virtual ethnography on digital memes was conducted to study discursive structures –mythologies, imaginaries, symbols, and narratives– in the #FuckGenderRoles cyber campaign. Critical Discourse Analysis and Multimodal Analysis are used to carry out a case study of a cyber campaign launched in Spain in 2019. The study concludes that there is an interdependence between logical positions and mythical structures that promote feminism as a way to integrate diversity and that echo traditional mythical characters in their modes of explanation.
Keywords: cyberculture; cyberfeminism; Digital ethnography; discourse analysis